The designed by Brazil football - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
The theme of football is not, on the part of the great majority of historians and academics, attention. At least until the late 1970s and early 1980s. Many see it as something minor. Perhaps because of prejudices acquired through the vision of anarchists, anarchosyndicalists, socialists and communists, who saw in sport a factor of alienation from the cause of the working class. Perhaps because it was used as a vehicle for a popularization of governments, especially in the military period. Perhaps more recently, allegations of corruption during the organization of the 2014 World Cup in Brazil. There is no denying that, particularly Brazil, a physical practice is embedded in social relations, as such, subject to new participations, new senses and new meanings. In this way, it is an integral part of the changes engendered by the Brazilian historical process. In this way, to despise the theme is to reject the daily, the playful, the feeling that permeates generations, where dissatisfactions, frustrations and exploitations are spilled, even without clarity, of a people who always fought, who continues fighting, even almost always following the sina of loss, of daily defeat. Football is a reflection of who we are and how we look at the world.
Keywords: Football; Proliferation; Imaginary; Social control